1975
DOI: 10.1177/000348947508400109
|View full text |Cite
|
Sign up to set email alerts
|

Tympanometric Pattern Classification in Relation to Middle Ear Effusions

Abstract: Tympanometric evaluation using an otoadmittance meter and X-Y plotter was performed on 129 ears of 70 children with history of recurrent acute otitis media, or evidence otoscopically of persistent middle ear effusion, or both. Myringotomy, performed immediately following the tympanometric procedure, confirmed the presence or absence of effusion. Following myringotomy, tympanometric patterns, as shown by susceptance and conductance tracings at 220 and 660 Hz, were identified and middle ear pressures and otoadmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

1976
1976
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 7 publications
2
23
0
1
Order By: Relevance
“…Acoustic Immitance measurement revealed a flat tympanogram with normal ear canal volume. Such findings are suggestive of a perforated tympanic membrane with active middle ear pathology (27). Acoustic reflex and otoacoustic emissions were not obtained probably because of the perforated tympanic membrane (28,29).…”
Section: Discussionmentioning
confidence: 98%
“…Acoustic Immitance measurement revealed a flat tympanogram with normal ear canal volume. Such findings are suggestive of a perforated tympanic membrane with active middle ear pathology (27). Acoustic reflex and otoacoustic emissions were not obtained probably because of the perforated tympanic membrane (28,29).…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have suggested that tympanometry may provide a method to evaluate middle ear ventilation that requires less experience and subjective interpretation on the part of the examiner than previous methods (Beery et al, 1975;Brooks, 1968;Paradise et al, 1976;Shurin et al, 1977). It has been used successfully in routine clinical screening of pediatric populations for middle ear defects and to detect and follow the results of middle ear effusions (Cante et al, 1980;Jerger, 1970;Paradise et al, 1980;Paradise et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…All measurements were performed by one investigator to minimize potential discrepancies in technique, although other studies (Beery et al, 1975;Brooks, 1968;Paradise et al, 1976;Shurin et al, 1977) suggest there is very little difference in measurements by different operators using standard procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Equally undoubtedly, pure-tone screening is inefficient in identifying children at risk. Several studies have indicated that school screening, even if carried out with the utmost rigour, is only about 50% efficient in identifying children with MEE, which is by far the major cause of auditory dysfunction (Eagles 1972, Beery et al 1975, Cody et al 1975, Cunningham & McArthur 1981). By contrast, impedance measurement has a sensitivity of over 90% and a specificity of the same order (Brooks 1982).…”
mentioning
confidence: 99%